1. 4x + 3y = -2
2. x - y = -4
Multiplying 2. by 3 gives: (we have done this so that we end up with a -3y)
3. 3x - 3y = -12
1. added to 3. gives: (now, by adding, the 3y & -3y will cancel out)
4. 7x = -14 (the 4x + the 3x gives 7x, the y's cancel out, -2 + -12 gives -14)
thus x = -14/7
x = -2
Substituting x = -2 into 1. gives
(4 * -2) + 3y = -2
-8 + 3y = -2
3y = -2 + 8
3y = 6
y = 2
Thus x = -2 and y = 2.
Chat with our AI personalities
4xy+1=3y-7x 4xy-3y=-7x-1 y(4x-3)=-7x-1 y=(-7x-1)/(4x-3)
xy(3x - 2y)(2x + 3y)
mid point of xy
y(z+x) + 4(x+z)
y = x/(x - 3) so y(x - 3) = x xy - 3y = x xy - x = 3y x(y - 1) = 3y x = 3y/(y - 1) for y ≠1 So, the inverse function is f(y) = 3y/(y - 1) where y ≠1